2007
DOI: 10.1177/0363199006297507
|View full text |Cite
|
Sign up to set email alerts
|

Creating Virtual Families? The Bequeathing Practices of Childless Single and Widowed Testators in 1951 and 2000 in Ireland

Abstract: This article is drawn from my PhD dissertation, which explores bequeathing practices in the second half of the twentieth century in Ireland. In particular, this article compares the bequeathing practices of childless single and widowed people in Irish society in 1951 and 2000 through a qualitative analysis of probated wills to answer the questions: In the absence of spouses and children, to whom did they leave their property? Did bequeathing practices change in the fifty-year period during which Ireland underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Auten and Joulfaian (1996) showed that when children are financially better off, parents are more inclined to leave larger charitable bequests. While Whitaker (2007) found that the majority of childless single and widowed people in Ireland left bequests to their extended families: siblings, nieces, nephews, and cousins, rather than to the masses or charity. Generally speaking we expect that the presence of spouses and children (or grandchildren) will decrease the likelihood of leaving a charitable bequest.…”
Section: Family Statusmentioning
confidence: 99%
“…Auten and Joulfaian (1996) showed that when children are financially better off, parents are more inclined to leave larger charitable bequests. While Whitaker (2007) found that the majority of childless single and widowed people in Ireland left bequests to their extended families: siblings, nieces, nephews, and cousins, rather than to the masses or charity. Generally speaking we expect that the presence of spouses and children (or grandchildren) will decrease the likelihood of leaving a charitable bequest.…”
Section: Family Statusmentioning
confidence: 99%
“…The presence of close relatives in need of financial support is an important factor limiting charitable giving and charitable bequests (Whitaker, 2007). As argued earlier, people need to believe that they and their families will be financially secure, now and in the future, before they are willing to make significant charitable donations and bequests.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Research has been able to identify personal characteristics associated with will makers, for example, older age (Humphrey et al, 2010;State Trustees Limited, 2012), female gender (Baker & Gilding, 2011;Gaffney-Rhys & Jones, 2013), being married or in a relationship (Humphrey et al, 2010;Wilson & Tilse, 2012), being/becoming a parent (Baker & Gilding, 2011;Olsberg & Winters, 2005), and having a high value estate (Dekker & Howard, 2006;Olsberg & Winters, 2005). There are, however, some conflicting findings relating to whether being a parent (Wilson & Tilse, 2012) and having greater financial worth (State Trustees Limited, 2012;Whitaker, 2007) differentiate will makers from nonwill makers. There is less understanding of circumstances or events that motivate an individual to prepare a will.…”
mentioning
confidence: 99%